COVID-19 amongst cancer patients: an experience from Oman - Bassim Jaffar Al Bahrani; Itrat Mehdi; Faryal Ali Khamis; Abdulaziz Mohammed Al Farsi; Fatma Al Fahdi; Najla Ali Al Lawati (Journal of the Pakistan Medical Association, 2021)
Introduction: The pandemic of coronavirus has no parallel in recent history. Human Life has completely transformed. There are no approved standard therapies. Patients with comorbidities, old age, immunocompromised, and cancer are at higher risk of complicated course and higher mortality. Patients and Methods: This study is an analysis of Cancer patients who got COVID-19 infection to assess the rate, demographics, laboratory data, and mortality. The data was compared, with normal non-cancer COVID-19 infected patients. Results: The overall number of COVID-19 positive cancer patients was low (0.47%) compared to normal population (2.17%). The mortality in COVID-19 Positive cancer patients was 35.1% vs 1.03%. Diabetic, hypertensive and cardiac patients are more likely to get COVID-19. Among Normal subjects, ratio of expatriate patients was higher. Septicemia was more frequent in cancer patients. Non-cancerous patients were more commonly ventilated. Leucocytosis, renal impairment, Hypocalcemia, high Troponin, high D-dimer, and high transaminases were seen more in non-cancerous patients. A high Lactate dehydrogenase was more common in cancer patients. The mortality from COVID-19 was higher in cancer patients 25% vs 15.7%. Around 72.8% cancer patients received active treatment with in past 4 weeks before COVID-19 infection. Discussion and Conclusions: There are very few reports of COVID-19 infection in cancer patients. The number of patients is small with limited information and capacity of the healthcare system. Oncologists should consider to tailor cancer clinical management. The cancer patients must practice social distancing, and seek early evaluation for symptoms suspicious for COVID-19, testing for virus and chest radiography. Contintuous...